POLA KOMUNIKASI KELOMPOK PRAMUKA PENEGAK DALAM PEMBINAAN KARAKTER PATRIOTIK PADA KWARTIR RANTING UJUNG BATU KABUPATEN ROKAN HULU - Jai Rahmandani; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
A group is an interaction and communication from people who have planto achieve a common goal. One of them is a communication group of scoutenforcer in coaching patriot characteristic of twig quarter Ujungbatu of RokanHulu regency. They do interaction and communication to achieveing success incoaching They do interaction and communication to achieveing success incoaching scouts in twig qwarter of Ujungbatu. The purpose of this research is tofind out the function of communication group of scout enforcer in coachingpatriot characteristic of twig quarter Ujungbatu of Rokan Hulu regency ,as wellas how to pattern of communication group of scout enforcer in coaching patriotcharacteristic of twig quarter Ujungbatu of Rokan Hulu regency.This research uses qualitative methods with descriptive approach.Subject of this research consisted of two scout couches SMK Pemdes Ujungbatu,one people council chif work the twig, and two chif support or scout leader. Datacollected through in-depth interviews, observation, and documentation. Toachieve the validity of the data in this study, the authors used the extension ofparticipation and triangulation.The results of this reserch function communication group used in scoutcoaching is a function of social relations, education, persuasion and problemsolving. Than this communication paternt of scout enforcer twig quarterUjungbatu is done through a one way and two way, and interaction whichoccured with anyone among trainers and coaches, with using a communicationnetworks of star or all pattern shapping channe. In this case to form patriotcharacteristic of twig quarter scout Ujungbatu of Rokan Hulu regency is donethrough a implementing tri satya and dasa darma of scout.Keywords: Boy scouts, group Communicatio